Efficacy and safety of Eribulin-based chemotherapy in HER2 negative advanced breast cancer patients: a real-world study - Li, Yuting; Han, Dan; Hu, Ting; Xiong, Jie; Wang, Yuehua; Zhao, Yanxia (Frontiers in Oncology, 2025)
BackgroundBreast cancer is recognized as one of the most common cancers worldwide, exhibiting a notably high incidence rate among women in China. Despite significant advancements in therapeutic approaches, the prognosis for patients diagnosed with advanced stages of the disease remains poor. Therefore, there is an urgent necessity to investigate the effectiveness and safety of treatments such as Eribulin, a non-taxane microtubule inhibitor that is recommended for use beyond second-line therapy.MethodsThis retrospective multicenter study assessed 105 patients with HER2-negative advanced breast cancer who received Eribulin treatment from 2020 to 2023.ResultsWith a median follow-up of 13.3 months, the median progression-free survival (PFS) was 6.0 months. Patients on early-line Eribulin had a significantly longer PFS (6.7 vs. 4.9 months, P = 0.038) than those on later lines. Combination therapy tended toward longer PFS than monotherapy (6.4 vs. 4.9 months; P = 0.319), albeit non-significantly. Combinations with PD-1 inhibitors or chemotherapy had a higher PFS than those with anti-angiogenic agents (P = 0.022). Among ER-negative patients in the combination therapy subgroup, HER2-zero tumors had a significantly longer PFS than HER2-low tumors (9.5 vs. 4.1 months, P = 0.026). The most frequently observed adverse events were hematological toxicity, with the majority classified as manageable in severity.ConclusionThe findings emphasize the potential of Eribulin in the treatment of HER2-negative advanced breast cancer, highlighting the need for further large-scale, prospective studies to refine and enhance treatment strategies.